The Influence Of Competence, Motivation And Work Environment On The Performance - Desmawati, D.; Riyadi, Ari Slamet (Golden Ratio of Human Resource Management, 2021)
The purpose of this study is whether Competency, Motivation, and Work Environment have a positive and significant influence and which variable has the dominant influence on the Performance of Employees at the Watang Sawitto District Office in Pinrang Regency. The research method uses secondary data and primary data on 30 samples, the data collection methods used are observation, documentation, interviews, and questionnaires. The analysis model used is descriptive statistics and multiple regression analysis. The results of the study show that 1) Competence has a positive but not significant effect on the performance of employees at the Watang Sawitto District Office in Pinrang Regency. 2) Motivation has a positive and significant effect on the performance of employees of the Watang Sawitto District Office in Pinrang Regency. 3) The work environment has an effect but not significant on the performance of employees of the Watang Sawitto District Office in Pinrang Regency. 4) Motivation has a dominant effect on the performance of staff at the Watang Sawitto District Office in Pinrang Regency.